Respostas
respondido por:
0
a) I. Tradução algébrica das informações
Cancela o +y com o - y
2x = 27
x = 27/2
x = 13,5
x + y = 18
13,5 + y = 18
y = 18 - 13,5
y = 4,5
III . Comprovação
x + y = 18
13,5 + 4,5 = 18
18 = 18
x - y = 9
13,5 - 4,5 = 9
9 = 9
b) I. Tradução algébrica das informações
Cancela o -y com +y
3x = 15
x = 15/3
x = 5
x - y = 2
5 - y = 2
y = 3
III . Comprovação
x - y = 2
5 - 3 = 2
2 = 2
2.x + y = 13
2 . 5 + 3 = 13
10 + 3 = 13
13 = 13
Cancela o +y com o - y
2x = 27
x = 27/2
x = 13,5
x + y = 18
13,5 + y = 18
y = 18 - 13,5
y = 4,5
III . Comprovação
x + y = 18
13,5 + 4,5 = 18
18 = 18
x - y = 9
13,5 - 4,5 = 9
9 = 9
b) I. Tradução algébrica das informações
Cancela o -y com +y
3x = 15
x = 15/3
x = 5
x - y = 2
5 - y = 2
y = 3
III . Comprovação
x - y = 2
5 - 3 = 2
2 = 2
2.x + y = 13
2 . 5 + 3 = 13
10 + 3 = 13
13 = 13
Anexos:
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás